Isolated lymphoma of the choroid plexus: a case report - Ali Msheik; Ayman Mawassi; Zeinab Al Mokdad (Exploration of Neuroscience)
The choroid plexus, pivotal for cerebrospinal fluid (CSF) regulation and blood-CSF barrier function, becomes a focal point for primary central nervous system lymphoma (PCNSL). This article delves into a case of this uncommon presentation, highlighting diagnostic challenges, treatment complexities, and post-treatment outcomes. A 30-year-old Lebanese patient with mild headaches and vomiting was initially diagnosed with vasculitis but later confirmed through endoscopic biopsy to have diffuse large B-cell lymphoma of the choroid plexus. Treatment with intravenous methotrexate, intrathecal cytarabine, rituximab, and radiotherapy led to gradual neurological improvement. Treatment strategies, aligned with PCNSL standards, include intravenous methotrexate, intrathecal cytarabine, rituximab, and radiotherapy, leading to gradual neurological improvement post-treatment. Prognostic factors, such as age and specific brain area involvement, guide tailored treatment plans. This report emphasizes the need for a multidisciplinary approach, increased awareness, and ongoing research for optimal outcomes in PCNSL cases involving the choroid plexus.